Determinan Faktor Penyebab Dismenore pada Remaja Putri di Desa Lubuk Sukon Kecamatan Ingin Jaya Kabupaten Aceh Besar Tahun 2022 - Yuli Zuhkrina; Martina Martina (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Menstrual is the process of the release of the endometrium physiologically where there are many blood vessels, who take place every once a month. But there were several problems that a possible at the time menstrual, one of them is dysmenorrhea, of a back, pain head. Problem painful menstruation (dysmenorrhea) to a problem often complained by woment at when they sought treatment to the doctor or health workers. Pain because imbalance progesterone so as to cause abdominal cramps the bottom even up to the waist. Prostaglandins that high levels will result in contraction the more powerful, so that the pains that percelved has also strong. The kind of research is quantitative with the design descriptive approach in cross sectional study. Research located village the Lubuk Sukon, time of the research commenced on the 10 up to 15 October 2022. Population even all adolescent girls was 11 up to 20 years were 70 respondents. The sample overall sampling. Data collection through the distribution of the questionnaire. Design data analysis use univariat and bivariat analysis, and analysis using the chi-square α = 0,05 (degrees trust 95%). Conclusion is them relations between the ages of menarche, family history and behavior eat with dysmenorrhea in adolescent girls.